The Urgency of Law Enforcement for Sexual Violence Based on Law Number 12 of 2022 - Irda Nur Khumaeroh; Muhamad Iqbal Ansori Firdaus; Angga Riswanto (Indonesian Journal Publisher, 2025)
This study examines the regulatory construction of sexual violence crimes under Law Number 12 of 2022 concerning Sexual Violence Crimes (TPKS Law) and analyzes the urgency of effective law enforcement in Indonesia. The research applies a normative juridical method using historical and statutory approaches to explain the background, development, and legal framework of the TPKS Law. The historical approach traces the evolution of legal protection for victims of sexual violence, while the legislative approach analyzes the substance, structure, and systematic coherence of the law within the national legal system. The findings show that the TPKS Law consists of 12 chapters and 93 articles that comprehensively regulate sexual violence crimes. These provisions include general definitions, classifications of sexual violence, related criminal acts, investigation and prosecution procedures, and court examination mechanisms. The law also explicitly regulates the rights of victims, victims’ families, and witnesses, including protection, recovery, restitution, and access to justice. TPKS Law prioritizes integrated women/children protection services at national and local levels, plus prevention, coordination, oversight, and community involvement. It includes funding, global partnerships, transitional clauses, and final provisions, notably launching SPPT-PKKTP for women violence cases. Within this system, victims are positioned as legal subjects with the right to be heard, informed of legal processes, considered in the pursuit of justice, and restored from the impacts of violence. This victim-centered orientation represents a shift toward restorative-justice.